Human Metapneumovirus as a causative agent of acute bronchiolitis in infants - Xepapadaki, P.; Psarras, S.; Bossios, A.; Tsolia, M.; Gourgiotis, D.; Liapi-Adamidou, G.; Constantopoulos, A. G.; Kafetzis, D.; Papadopoulos, N. G. (J Clin Virol, 2004)
Human Metapneumovirus (hMPV), has been recently isolated from children with acute respiratory tract infections (RTIs), including bronchiolitis, and classified in the Pneumovirinae subfamily within the Paramyxoviridae family.|Since most bronchiolitis studies fail to detect any viral pathogen in part of the samples, we sought for the presence of hMPV in a well characterized bronchiolitis cohort.|Nasal washes were obtained from 56 children admitted to the hospital for acute bronchiolitis. RNA extraction and subsequent RT-PCR were used to detect hMPV, and correlated the presence of the virus with clinical characteristics of the disease.|PCR revealed the presence of hMPV in 16% of bronchiolitis cases, whereas respiratory syncytial virus (RSV; 67.9%) was the most frequently encountered viral pathogen. hMPV was identified either as a unique viral pathogen or co-existed with RSV, with whom they shared a similar seasonal distribution. There were no differences in disease characteristics, either clinical or laboratory, between bronchiolitis cases where hMPV was present and those caused by RSV or other viral pathogens. These findings suggest that hMPV is a common and important causative agent in infants with bronchiolitis, with clinical characteristics similar to that of RSV.
Keywords: Acute Disease Bronchiolitis; Viral Humans Infant Metapneumovirus Nasopharynx Paramyxoviridae Infections Polymerase Chain Reaction Seasons